2005
DOI: 10.1038/ng1535
|View full text |Cite
|
Sign up to set email alerts
|

An empirical test of the mutational landscape model of adaptation using a single-stranded DNA virus

Abstract: The primary impediment to formulating a general theory for adaptive evolution has been the unknown distribution of fitness effects for new beneficial mutations. By applying extreme value theory, Gillespie circumvented this issue in his mutational landscape model for the adaptation of DNA sequences, and Orr recently extended Gillespie's model, generating testable predictions regarding the course of adaptive evolution. Here we provide the first empirical examination of this model, using a single-stranded DNA bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
242
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(255 citation statements)
references
References 16 publications
8
242
3
Order By: Relevance
“…Key parameters such as N 0 and r could be manipulated experimentally, while parameters like s b and u could be measured in nonpermissive conditions (e.g., measuring the mutation rate to an antibiotic resistance allele). In organisms such as bacteriophage that have sufficiently small genomes, wholegenome sequencing could be used to confirm that adaptation occurred via single substitutions (e.g., Rokyta et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Key parameters such as N 0 and r could be manipulated experimentally, while parameters like s b and u could be measured in nonpermissive conditions (e.g., measuring the mutation rate to an antibiotic resistance allele). In organisms such as bacteriophage that have sufficiently small genomes, wholegenome sequencing could be used to confirm that adaptation occurred via single substitutions (e.g., Rokyta et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These efforts have largely focused on identifying patterns that might characterize adaptation through DNA sequence space (reviewed in Orr 2005). This work has revealed several interesting patterns (Gillespie 1984;Orr 2002Orr , 2005Rozen et al 2002) and has motivated a number of new experiments (Rozen et al 2002;Sanjuan et al 2004;Rokyta et al 2005;Barrett et al 2006;Kassen and Bataillon 2006). Nearly all work on the theory of adaptation, however, has been limited in at least one important way: it assumes that populations maintain a stable size following a sudden change in environment, a change to which the population must adapt.…”
mentioning
confidence: 99%
“…The model explained these patterns by positing that most single mutations were near or in excess of the optimum and adding the second mutation therefore resulted in a movement away from the optimum. In the present work, we attempted to shift the wild-type genotype, ID11, and its nine previously described beneficial mutations (Rokyta et al 2005(Rokyta et al , 2008(Rokyta et al , 2011 closer to and farther from the optimal phenotype by changing the temperature at which fitness was measured, to quantify the changes in fitness effects and patterns of epistatic interactions between mutations. Previous work has shown that close relatives of ID11 in the G4-like group of microvirid coliphages (Rokyta et al 2006b) tend to have fitnesses inversely correlated with temperature (Knies et al 2009).…”
mentioning
confidence: 99%
“…An earlier paper by John on the concept of a protein space (12) has also had contemporary influence, in the light of new ideas on how to model the process of adaptive evolution of protein and DNA sequences (Orr 2003), and the availability of data from viral systems on the detailed steps that actually occur during such evolution (Rokyta et al 2005). Another paper with John Haigh showed that data on human haemoglobin variants in European populations indicated a recent bottleneck of small population size (13).…”
Section: Research and Writings While Employed At The University Of Sumentioning
confidence: 99%